Ellis-Van Creveld Syndrome: Prenatal Diagnosis, Molecular Analysis and Genetic Counseling - Chih-Ping Chen; Yi-Ning Su; Chin-Yuan Hsu; Schu-Rern Chern; Fuu-Jen Tsai; Pei-Chen Wu; Po-Tsang Chen; Wayseen Wang (Elsevier, 2010)
Objective: To present the perinatal findings and molecular genetic analysis of two siblings with Ellis-van Creveld (EvC) syndrome. Materials, Methods and Results: A 33-year-old woman, gravida 3, para 1, was referred for genetic counseling at 18 gestational weeks because of recurrent fetal skeletal dysplasia. Two years previously, she had delivered a 1,316-g dead male baby at 28 gestational weeks with a karyotype of 46,XY, postaxial polydactyly of the hands, thoracic narrowness, endocardial cushion defects, transposition of the great arteries, shortening of the long bones, malposition of the toes, and hypoplastic nails. During this pregnancy, prenatal ultrasound at 18 gestational weeks revealed shortening of the long bones (equivalent to 15 weeks), postaxial polydactyly of both hands, thoracic narrowness, and endocardial cushion defects. The pregnancy was subsequently terminated, and a 236-g female fetus was delivered with a karyotype of 46,XX, postaxial polydactyly of the hands, thoracic dysplasia, endocardial cushion defects, shortening of the long bones, and malposition of the toes and hypoplastic nails. The phenotype of each of the two siblings was consistent with EVC syndrome. Molecular analysis of the EVC and EVC2 genes revealed heterozygous mutations in the EVC2 gene. A heterozygous deletion mutation of a 26-bp deletion of c.871-2_894del26 encompassing the junction between intron 7 and exon 8 of the EVC2 gene was found in the mother and two siblings, and a heterozygous nonsense mutation of c.1195C >T, p.R399X in exon 10 of the EVC2 gene was found in the father and two siblings. Conclusion: Prenatal sonographic identification of endocardial cushion defects in association with shortening of the long bones should alert clinicians to the possibility of EvC syndrome and prompt a careful search of hexadactyly of the hands. Molecular analysis of the EVC and EVC2 genes is helpful in genetic counseling in cases with prenatally detected postaxial polydactyly, thoracic narrowness, short limbs and endocardial cushion defects.